(untitled) (Research, Society and Development, 2022)
In Brazil, Prostate Cancer (PCa) is the second most common in men and has a high rate of morbidity and mortality. Therefore, the importance of early screening from the age of 50 is recommended. Given that, this study aims to analyze the screening and diagnosis difficulties encountered in Primary Health Care (PHC) for PCa prevention. This is an integrative literature review study, with a search performed mutually by two researchers in the Virtual Health Library (VHL), Scielo and PubMed, by crossing the descriptors “prostate cancer”, “screening” and “diagnosis”, using the Boolean operator and. To carry out the search and selection of articles, the following elegibility criteria were used: productions from the last two years; fully available for free; and published in Portuguese, English and Spanish. The initial search resulted in 488 articles, of which 105 met the adopted eligibility criteria. Of those, excluded the duplications, seven were selected to compose the corpus of the review because they meet the objective of the study. It was possible to identify factors that make it difficult for men to make a decision to perform PCa screening and diagnosis, especially beliefs, male self-vulnerability and medical communication. Besides, differences were found among health professionals about the standardization of criteria for screening. We emphasize the need for constant research in order to identify the difficulties of PCa screening and diagnosis.